Intestinal mucus affinity and biological activity of an orally administered antibacterial and anti-inflammatory peptide. Issue 2 (7th May 2014) - Dupont, Aline; Kaconis, Yani; Yang, Ines; Albers, Thorben; Woltemate, Sabrina; Heinbockel, Lena; Andersson, Mats; Suerbaum, Sebastian; Brandenburg, Klaus; Hornef, Mathias W
Abstract : Objective: Antimicrobial peptides (AMP) provide protection from infection by pathogenic microorganisms and restrict bacterial growth at epithelial surfaces to maintain mucosal homeostasis. In addition, they exert a significant anti-inflammatory activity. Here we analysed the anatomical distribution and biological activity of an orally administered AMP in the context of bacterial infection and host–microbial homeostasis. Design: The anatomical distribution as well as antibacterial and anti-inflammatory activity of the endogenous AMP cryptdin 2 and the synthetic peptide Pep19-2.5 at the enteric mucosal surface were analysed by immunostaining, functional viability and stimulation assays, an oral Salmonella enterica subsp. enterica sv. Typhimurium (S. Typhimurium) model and comparative microbiota analysis. Results: Endogenous cryptdin 2 was found attached to bacteria of the enteric microbiota within the intestinal mucus layer. Similarly, the synthetic peptide Pep19-2.5 attached rapidly to bacterial cells, exhibited a marked affinity for the intestinal mucus layer in vivo, altered the structural organisation of endotoxin in a mucus matrix and demonstrated potent anti-inflammatory and antibacterial activity. Oral Pep19-2.5 administration induced significant changes in the composition of the enteric microbiota as determined by high-throughput 16S rDNA sequencing. This may have contributed to the only transient improvement of the clinical symptoms after oral infection with S. Typhimurium. Conclusions: Our findings demonstrate the anti-inflammatory activity and mucus affinity of the synthetic AMP Pep19-2.5 and characterise the influence on microbiota composition and enteropathogen infection after oral administration.